Big Hitters: Important Factors Characterizing Team Effectiveness in Professional Cricket - Webster, Leonie V.; Hardy, James; Hardy, Lew (Frontiers in Psychology, 2017)
While organizational psychology attests to the multidimensional nature of team effectiveness, insight regarding the most important factors contributing to the effectiveness of sports teams, especially elite teams, is lacking. An abductive method of qualitative enquiry was adopted to capture participants’ construal of team effectiveness, drawing on the extant literature in both sport and organizational psychology. Semi-structured interviews were conducted with 21 players, coaches, and psychologists involved in elite cricket, with resultant data analyzed inductively initially, before being reanalyzed deductively. Although the narratives endorsed the value of many of the deductively derived factors, other constructs more prominent in organizational psychology (e.g., trust and intra-group conflict) appeared to be more important than traditional sport psychology group factors. The results revealed six broad themes; culture and environment, values, communication, understanding, leadership, and unique individuals, with some gender differences apparent throughout. Based on our elite sample’s construal of team effectiveness, we propose a new model representing a practical, parsimonious, and novel conceptualization of the most important attributes of team effectiveness in cricket, with conceivable transferability to other team sports.